Evaluation and Optimization Strategies of Environmental Protection Performance for Passenger Seats of EMU. Issue 4 (January 2021) - Jia, Xu; Zhan, Xue; Zhou, Xinhong; Chen, Chuanhai; Jin, Tongtong
Abstract: Passenger seats of Electric multiple-unit (EMU) influence environmental performance. Formaldehyde and other volatile organic compounds in the nonmetallic material of the seat is volatized. Toxic gas is produced by seat material combustion. This study chooses a typical passenger seat and proposes optimization strategies based on the experiment. First, the source of seat formaldehyde and volatile organic compounds is determined through a test. Four optimization strategies, including foaming pretreatment, foaming formula improvement, binder optimization, and bioenzyme spraying, are proposed. Second, the source of toxic gases in the seat is determined through a combustion test on the seat and its nonmetallic materials. Moreover, the optimization strategy for controlling the material of seat fabric is formulated.